The Responsibility of Government and Society Towards Social Cohesion: A Family Perspective (The Strategic Review for Southern Africa, 2021)
AbstractSocial cohesion, the foundation that keeps society together, is influenced by various inter-related factors such as education social, cultural, religious, and business, among others. Current debates indicates that unless social cohesion in its various dimensions is addressed, be it through reconciliation, tackling inequality, crafting a national identity, or bridging rural-urban divides, the implementation of any Southern African Development Plan will be challenging. In this paper, social cohesion is viewed as an intervention for coexistence; as an invitation to find common ground and allowing the sharing of social spaces; and to forge a common identity whilst recognising societal diversity. This paper postulates that although social cohesion is intended to contribute towards nation-building and national unity, government policies are fundamental to the advancement thereof. The paper defines, unpacks, and identifies the challenges of social cohesion using South Africa as a case study. The paper argues that the family is instrumental in building social cohesion. Government through its policies processes has an important role to play in strengthen the family. The lessons learnt could contribute to the role of family towards social cohesion on the African continent.